International Standards of Social Protection of Internally Displaced Persons: Administrative and Criminal Aspects - Kobrusieva, Yevheniiа; Leheza, Yevhen Oleksandrovych; Rudoi, Kateryna; Shamara, Oleksandr; Chalavan, Viktor (Jurnal Cita Hukum, 2021)
This article reveals the problem of social security of internally displeased persons. The scope of social protection directed at this category of population is not the same in different countries. Taking into account the origin of the authors of the article, the questions of social protection of internally displaced persons in Ukraine are described in detail. Conclusions. Special attention was paid to the need to provide people with the opportunity to exercise their rights and freedoms as well as the proper conditions for social rehabilitation, that has arisen before the state. As a result of the research – ways how to strengthen the social security, increase the level of social protection and make it more effective are proposed. The European standards of social protection of internally displaced persons are a set of norms fixed in the acts of the Council of Europe, the European Union, decisions of the European Court of Human Rights, which, as a result of their implementation in the internal law of the states become mandatory for implementation and determine the decent living conditions of internally displaced persons, the responsibilities of the state in this area for ensuring security and full decent development of personality. In the system of European standards for social protection of internally displaced persons, the relevant norms developed by various institutions of the Council of Europe are extremely important.Keywords: Social Protection; Social Security; Internally Displaced Persons; Displacement Standar Internasional Perlindungan Sosial Bagi Pengungsi Internal: Aspek Administratif dan Criminal Abstrak. Artikel ini mengungkapkan masalah jaminan sosial orang-orang yang tidak senang secara internal. Cakupan perlindungan sosial yang ditujukan pada kategori penduduk ini tidak sama di berbagai negara. Mempertimbangkan asal usul penulis artikel, pertanyaan tentang perlindungan sosial bagi para pengungsi internal di Ukraina dijelaskan secara rinci. Kesimpulan. Perhatian khusus diberikan pada kebutuhan untuk memberikan orang kesempatan untuk menggunakan hak dan kebebasan mereka serta kondisi yang tepat untuk rehabilitasi sosial, yang telah muncul sebelum negara. Sebagai hasil penelitian diusulkan cara bagaimana memperkuat jaminan sosial, meningkatkan tingkat perlindungan sosial dan membuatnya lebih efektif. Standar Eropa tentang perlindungan sosial bagi pengungsi internal adalah seperangkat norma yang ditetapkan dalam tindakan Dewan Eropa, Uni Eropa, keputusan Pengadilan Hak Asasi Manusia Eropa, yang, sebagai hasil dari implementasinya dalam hukum internal. negara menjadi wajib untuk implementasi dan menentukan kondisi kehidupan yang layak dari orang-orang yang dipindahkan secara internal, tanggung jawab negara di bidang ini untuk memastikan keamanan dan pengembangan kepribadian yang layak sepenuhnya. Dalam sistem standar Eropa untuk perlindungan sosial bagi pengungsi internal, norma-norma relevan yang dikembangkan oleh berbagai lembaga Dewan Eropa sangat penting.Kata kunci: Perlindungan Sosial; Jaminan Sosial; Pengungsi Internal; Pengungsian Международные стандарты социальной защиты внутренне перемещенных лиц: административные и уголовные аспекты Аннотация. В статье раскрывается проблема социальной защищенности внутренне недовольных. Объем социальной защиты, направленной на эту категорию населения, в разных странах неодинаков. С учетом происхождения авторов статьи подробно освещены вопросы социальной защиты внутренне перемещенных лиц в Украине. Выводы. Особое внимание было уделено необходимости предоставить людям возможность реализовать свои права и свободы, а также создать соответствующие условия для социальной реабилитации, которые возникли перед государством. В результате исследования - предложены способы, как усилить социальную защищенность, повысить уровень социальной защиты и сделать ее более эффективной. Европейские стандарты социальной защиты внутренне перемещенных лиц - это совокупность норм, закрепленных в актах Совета Европы, Европейского Союза, решениях Европейского суда по правам человека, которые в результате их имплементации во внутреннее право государств становятся обязательными для реализации и определяют достойные условия жизни вынужденных переселенцев, обязанности государства в этой сфере по обеспечению безопасности и полноценного достойного развития личности. В системе европейских стандартов социальной защиты внутренне перемещенных лиц чрезвычайно важны соответствующие нормы, разработанные различными учреждениями Совета Европы.Ключевые слова: Социальная Защита; Социальное Обеспечение; Внутренне Перемещенные Лица; Перемещение